Effect of different incision sites of phacoemulsification on trabeculectomy bleb function: prospective case-control study - Mohamed Anbar; Hatem Ammar (BMC Ophthalmology, 2017)
Abstract Background The aim of this study was to compare superior and temporal clear corneal incisions of uneventful phacoemulsification and in-the-bag intraocular lens implantation on intraocular pressure control and the bleb morphology in eyes that have undergone previous successful trabeculectomy. Methods In this Prospective case-control study, a total of 100 eyes of 100 patients previously undergone trabeculectomy without antimetabolites, divided into two groups. Group A (temporal group) including 50 patients underwent phacoemulsification with a temporal corneal incision and group B (superior group) including 50 patients underwent phacoemulsification with a superior corneal incision. Comparisons between the two groups were performed after one year of follow-up regarding Intraocular pressure changes, bleb morphology score using the Wuerzburg bleb classification score and any added glaucoma medications. Results At the last visit, the mean intraocular pressure for the temporal group was 17.55 ± 1.47 (p = 0.51) and for the superior group was 16.90 ± 1.71 (p = 0.85); the difference between the two groups was insignificant (p = 0.21). Regarding the bleb morphology, the mean bleb morphology score in the temporal group was 10.50 ± 0.95 (p = 0.19) and for the superior group was 10.20 ± 1.06 (p = 0.01).There was an insignificant difference in the bleb grading morphology regarding both groups (p = 0.35). Conclusion Our study demonstrates that phacoemulsification whether done with a clear temporal or clear superior wound, does not affect intraocular pressure, bleb morphology or function after one year of follow-up in eyes following previous successful trabeculectomy. Furthermore, cataract surgery may be performed safely in eyes with functioning filtering blebs. Trial registration ISRCTN91835217 ‘retrospectively registered’ Date Of registration 6/6/2017